EVALUASI KINERJA PEGAWAI DALAM MENJALANKAN TUGAS DI MASYARAKAT (STUDI KASUS DI KANTOR SATPOL PAMONG PRAJA KABUPATEN KUTAI BARAT) - Albet Tael (ADMINISTRASI PUBLIK, 2018)
This study aims to find the performance of employees in performing their duties at the office Satpol public order Kutai Barat, therefore the researchers to formulate hypotheses "Anticipated performance evaluation of employees in performing their duties in the Office Satpol public order Kutai Barat reached a minimum or equal to 65% ".The timing of the research was conducted in late December 2015 to April 2016 for 4 (four) months. The research method in this study is descriptive quantitative data obtained through direct observation to the field, interviews and distributing questionnaires to the speakers with a sample size of 70 (seventy) of respondents.Based on the calculations, it is known that the performance evaluation of employees in performing their duties in the office of the Civil Service Satpol West Kutai reached 70% from 65% is expected.While one sample t test gives the figure of 2.66 t-test and t-table = 1.99. Thus the t-count larger than t-table so that H0 rejected and Ha accepted which means the hypothesis is accepted.